Comparative analysis of AI attitudes among JMC students in Brazil and the US: a mixed-methods approach - Seo Hyunjin; da Silva Marcos Paulo; Jona Blessing; Iqbal Azhar; Burkett Kerstina Macy; Khan Haseena U.; Urbina Carreno Alfredo E. (Online Media and Global Communication)
This research examines perspectives, attitudes, and behavioral intentions regarding AI among college students in Brazil and the United States. We chose Brazil and the United States, as they are leading countries in terms of AI adoption in Latin America and North America, respectively.